PERSEPSI DAN PREFERENSI PENGGUNA TERHADAP PENAMBAHAN CHATBOT PADA WEBSITE UNIVERSITAS TEKNOLOGI SUMBAWA SEBAGAI INOVASI LAYANAN KOMUNIKASI - Aksara, Fena; Yamin, Ahmad (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
The purpose of this study was to see how the perceptions and preferences of website users at the University of Technology Sumbawa and to find out the percentage of user acceptance of Chatbot if used on the University of Technology Sumbawa website. The instrument used was a questionnaire through the Survey method. Before using the instrument, a validity and reliability test was carried out with 30 respondents. After the instrument was valid and reliable, it was distributed to 97 students of the University of Technology Sumbawa to become respondents. The results of this study indicate that the perception of website users towards the addition of Chatbot to the University of Technology Sumbawa website is seen from 3 indicators, namely 70.9% for responses, 79.5% for opinions, and 67.7% for assessments, which means that user perception assumes that the University of Technology Sumbawa website is a source of information that is still used, but in terms of communication services, the Call Center on the website has not become a responsive service for respondents. For website user preferences for adding Chatbots to the University of Technology Sumbawa website, it can be seen from 4 indicators, namely 77% for previous experience, 80.4% for completeness, 74.7 for Trends, and 78.9 for Continuity, which means that respondent preferences have been formed with the ease of using Chatbots on other websites, so they want the same convenience on the University of Technology Sumbawa website. Meanwhile, the use of Chatbots to provide better service to users at University of Technology Sumbawa is seen based on the percentage of descriptive statistics at 80.4% who stated that they strongly agree with the implementation of Chatbots on the University of Technology Sumbawa website with the characteristics of AI offered in the questionnaire, including: real-time chat responses, accurate and fast AI knowledge, availability of services at all times and so on. Keywords: Perception, Preferences, Public Relations, Chatbots on Websites